Pengembangan Game Edukatif Berbasis Crossword Puzzle Pada Materi Prasasti Peninggalan Kedatuan Sriwijaya di Kelas X SMA Negeri 1 Indralaya Utara - Hartanti, Sri; Pahlevi, Muhammad Reza (Universitas Galuh, 2025)
The development of educational media in the form of educational games based on crossword puzzles was carried out using the Research and Development method with the Alessi & Trollip model. The media was validated by experts in subject matter, language, and media, showing very high validity results, namely 100% from media experts and 92.85% from subject matter experts. The practicality of the media was measured through a beta test involving teachers and students, with an average response of 97.78%, which is classified as very practical. This educational game was applied to material on the inscriptions left behind by the Sriwijaya Kingdom and was proven to increase student engagement in learning and foster an interest in studying history. This medium makes the learning process more meaningful and provides a contextual approach to understanding past events. The development of educational games based on crossword puzzles adds innovation to historical learning media and helps students understand past events in a more in-depth and contextual manner. The implications of this study show that educational games can be an effective alternative medium in history learning. Further development and widespread application of this medium is recommended to increase motivation and in-depth understanding of history.